Developing a participatory research framework through serious games to promote learning for children with autism - Abd El-Sattar, Hussein Karam Hussein; Omar, Manal; Mohamady, Hoda (Frontiers in Education, 2024)
People with autism, or Autism Spectrum Condition (ASC), is becoming increasingly common worldwide. Since individuals with ASC vary in their skills and methods that work for one may not work for another, many technology designers find it challenging to engage effectively with this population. Serious games (SGs) offer an intelligent learning environment that supports lifelong learning for individuals with ASC. Despite the availability of several frameworks, the question of whether SGs for individuals with ASC can have a dedicated framework remains unresolved. The objective of this study is to create a general framework for the design of serious games that can be applied to a variety of SGs targeting individuals with autism. A new participatory research framework is presented to assist game designers and relevant stakeholders in developing effective SGs for people with ASC. Through participatory sessions and a design thinking process, this framework seeks to involve users and relevant stakeholders as “design partners” in the design process. The framework was employed in the development of a new SG, called SALY (Simulation, Attention, Learn, and PLAY), designed to improve attention span and emotion recognition in individuals with ASC. Three research questions are discussed, and the mixed-methods approach adopted for the investigation. Several usability metrics were used to evaluate the game’s effectiveness, efficiency, and user satisfaction. The results show that the proposed game holds significant potential and will be of interest to educators and learners alike.